PENGARUH KOMUNIKASI KEPALA SEKOLAH TERHADAP KINERJA GURU SEKOLAH DASAR NEGERI 7 INSIT - Reza Fahlevi; Ramdhan Witarsa; Masrul Masrul (Elementary School Teacher Education (PGSD), STKIP PGRI Sumenep, 2023)
Principal communication is an important factor in directing teacher performance to be better. This research aims to measure how much influence the principal's communication has on the performance of elementary school teachers. The method used in this research is a quasi-experimental method. This method has nine stages, namely: literature review, identifying and limiting research problems, developing research hypotheses, making research designs, conducting pretests, conducting experiments, conducting posttests, processing and analyzing data, and drawing conclusions. The research sample consisted of 10 teachers, consisting of 5 teachers in the experimental class and 5 teachers in the control class. The data collection technique used is the observation of teacher performance. The research instrument used was the teacher's performance observation sheet. The research results showed that communication by the principal had a significant and positive effect on the performance of elementary school teachers in the experimental class. The communication carried out by the school principal must be carried out continuously and the quality improved so that the teacher's performance in other aspects can develop.